Relationships between physical activity and quality of life in parent–child dyads with ASD - Song, Yu; Shen, Bo; Pang, Yanli; Dong, Liangshan (Frontiers in Psychology, 2025)
IntroductionAutism spectrum disorder (ASD) is characterized by core and associated symptoms that adversely affect the quality of life (QOL) of both children with ASD and their parents. Although physical activity (PA) has been shown to promote QOL and well-being, limited research has examined these associations within parent–child dyads in families affected by ASD.MethodsThis cross-sectional study recruited 85 parent–child dyads from two autism rehabilitation centers in Central China. Children had a mean age of 5.25 years, and 75.3% of parents were aged between 31 and 40 years. Partial Pearson correlation analyses were conducted to examine associations between children’s and parents’ PA levels and multiple domains of QOL, controlling for child age, sex, and symptom severity.ResultsSignificant reciprocal associations were observed between the PA levels of children with ASD and their parents. Specifically, children’s light-intensity physical activity (LPA) was positively associated with parents’ LPA (r = 0.351, p < 0.01) and with the psychological (r = 0.23, p < 0.05) and environmental (r = 0.26, p < 0.05) domains of parental QOL. No direct correlations were identified between parental PA and children’s QOL.DiscussionThese findings underscore the potential of LPA as a feasible and accessible form of joint activity that may support QOL within families of children with ASD. Framed through reciprocal determinism, the results highlight the interconnected roles of children’s PA (behavior), parents’ psychological well-being (personal factor), and the family context (environment). Further longitudinal and intervention studies are warranted to confirm these relationships and inform family-centered PA interventions.